Dogs from the Ig pile dwellings in the National Museum of Slovenia - László Bartosiewicz (Arheološki Vestnik, 2002)
Eight skull fragments from dogs as well as the lower carnassials (M1) of 37 dogs and 4 wolves were measured in order to reconstruct the size and physical type of these ancient animals during the evaluation of prehistoric animal bone artifacts from the 19th century excavations in the Ljubljana Marshes near Ig. The complete ulnae of two additional individuals were used in estimating the withers height of dogs kept at this site. In addition to comparing the dog carnassials to those of coeval wolves, cranial dimensions and withers heights were both compared to similar measurements of Roman period urban dogs, known for their remarkable variability in size. Finally, the results from Ig were studied in light of Neolithic to Bronze Age dog remains from lacustral settlements in Switzerland and northern Italy. These calculations reconfirm that the dogs found at Ig were of the turbary dog type (C. familiaris palustris), a form evaluated within a broader context in this article.